The antimicrobial and cytotoxic effects of a copper-loaded zinc oxide phosphate cement - Wassmann, Torsten (Clin Oral Investig, 2020)
OBJECTIVES: Evidence about modifications of dental luting materials to minimize biological failure at the “marginal gap” between teeth and fixed prosthodontics is scarce. We compared a copper-modified (Co-ZOP) and a conventional zinc oxide phosphate cement (ZOP) in terms of antimicrobial and cytotoxic potentials in vitro and in vivo. MATERIALS AND METHODS: Specimens of ZOP and Co-ZOP were characterized by the mean arithmetic roughness (Ra) and surface free energy (SFE). Powder components were examined using scanning electron microscopy (SEM). Energy-dispersive X-ray spectroscopy (EDX) showed elemental material compositions. In vitro microbial adhesion was shown using SEM, luminescence, and fluorescence assays. CCK-8 assays of mouse fibroblasts (L929) and human gingival fibroblasts (GF-1) were performed after 6, 24, and 48 h of specimen incubation. In vivo, ZOP and Co-ZOP specimens were applied intraorally for 12 h; biofilm accumulation was shown using SEM. RESULTS: Ra of ZOP and Co-ZOP showed no significant differences; SFE was significantly higher for Co-ZOP. EDX exhibited minor copper radiation for Co-ZOP, none for ZOP. In vitro fungal adhesion to Co-ZOP was significantly higher than to ZOP; in vitro streptococcal adhesion, cytotoxicity, and in vivo biofilm formation were not significantly different. CONCLUSIONS: Co-ZOP showed low surface allocations of copper with no improved antimicrobial properties compared with conventional ZOP in vitro or in vivo. CLINICAL RELEVANCE: Antimicrobial effects and low cytotoxicity of biomaterials are important for the clinical outcome. Based on our in vitro and in vivo results, no clinical recommendation can be given for the tested Co-ZOP.